1994
DOI: 10.1111/j.1432-2277.1994.tb01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cytomegalovirus infection and disease in renal transplant recipients: HLA-DR7 and triple therapy

Abstract: In a prospective study, an analysis of risk factors for the development of cytomegalovirus (CMV) infection and disease was performed on 77 renal allograft recipients. Twenty-five out of the 77 recipients (32%) had a CMV infection. Twenty-two of the recipients received triple immunosuppressive therapy (cyclosporin A, prednisolone, and azathioprine) while the remaining 55 received standard therapy (cyclosporin A and prednisolone). In 23 recipients (30%) acute rejection was diagnosed and the first positive parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We and others have observed variations in the incidence, severity, and consequences of viral activity in solid organ transplantation related to HLA matching (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several authors have observed that the incidence of CMV disease was more common when certain HLA antigens were present (3,6 -8,10 -13).…”
mentioning
confidence: 99%
“…We and others have observed variations in the incidence, severity, and consequences of viral activity in solid organ transplantation related to HLA matching (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several authors have observed that the incidence of CMV disease was more common when certain HLA antigens were present (3,6 -8,10 -13).…”
mentioning
confidence: 99%
“…Furthermore, the presence of certain HLA class II alleles (eg, DR7) in patients who receive transplants can significantly increase their risk of developing HCMV-associated complications. [7][8][9] In the present study we show that HCMV-specific CD4 ϩ T cells can display an unusual cross-reactivity toward alloantigens and may therefore have the potential to contribute toward transplant rejection or graft-versus-host disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have described the association between the occurrence of viral infection and disease and the presence of certain HLA antigens in the host (Stewart, Kelsall et al 1981;Baldwin, Claas et al 1983;Roenhorst, Tegzess et al 1985;Kraat, Christiaans et al 1994;Varga, Rajczy et al 2008). Many HLA antigens, including HLA-A2, HLA-A24, HLA-A32, HLA-B52, HLA-Bw4, HLA-DR6, HLA-DR11, HLA-DR15 and HLA-DQ3, were reported to increase the risk of CMV infection (Roenhorst, Tegzess et al 1985;Chen, Rocha et al 2001;Hodge, Boivin et al 2004;Fan, Meng et al 2006), although there were some conflict among the results (Gomez, Aguado et al 1993).…”
Section: Association Of Hla-dr With Strain-specific Antibodiesmentioning
confidence: 99%